2006
DOI: 10.1103/physreva.74.043602
|View full text |Cite
|
Sign up to set email alerts
|

Ramping fermions in optical lattices across a Feshbach resonance

Abstract: We study the properties of ultracold Fermi gases in a three-dimensional optical lattice when crossing a Feshbach resonance. By using a zero-temperature formalism, we show that three-body processes are enhanced in a lattice system in comparison to the continuum case. This poses one possible explanation for the short molecule lifetimes found when decreasing the magnetic field across a Feshbach resonance. Effects of finite temperatures on the molecule formation rates are also discussed by computing the fraction o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…A similar result for our experimental data was computed numerically in [8]. This value gives an upper limit to the temperature since it assumes adiabatic formation of molecules at all doubly occupied sites and a perfect 50:50 mixture of the spin states.…”
Section: Thermometry In the Optical Latticesupporting
confidence: 87%
See 1 more Smart Citation
“…A similar result for our experimental data was computed numerically in [8]. This value gives an upper limit to the temperature since it assumes adiabatic formation of molecules at all doubly occupied sites and a perfect 50:50 mixture of the spin states.…”
Section: Thermometry In the Optical Latticesupporting
confidence: 87%
“…In this configuration approximative solutions of this model are feasible [5,6,7,8]. In the Hubbard model the interactions between particles are parametrized only by the parameter U regardless of the physical details of the interaction.…”
Section: Introductionmentioning
confidence: 99%
“…So far, temperature has not been measured in a lattice since standard methods -such as observing the rounding-off of the Fermi surface -turned out to be dominated by the inhomogeneity of the trapping potential rather than by temperature [16]. However, we find that the occupancy of the lattice depends strongly on the temperature [17,18,19] and the conversion of pairs of atoms into molecules is a sensitive probe, similar to the case of harmonically trapped fermions [20].In a previous experiment, deeply bound molecules of bosonic atoms have been created in an optical lattice by photo-association and were detected by a loss of atoms [6,21]. There the binding energy is only determined by the atomic properties and does not depend on the external potential, nor can the scattering properties between the molecules be adjusted.…”
mentioning
confidence: 74%
“…While number distributions have been analyzed for bosonic [65,203,[205][206][207] and fermionic systems [116,204], this method has been extensively evaluated, specifically for thermometry, in fermionic systems where the number of atoms per site is limited to zero, one, and two [116,204]. The number of doubly occupied sites as a function of temperature in the Fermi-Hubbard model can be calculated from theory with relative accuracy in certain limits [116,184,204,208]. A comparison of QMC, DMFT, and series approximations demonstrated that simple series approximations give almost identical results to the more complex computational calculations in the parameter range of current experiments [116].…”
Section: In-situ Imagingmentioning
confidence: 99%